Consensus Aesthetics: The Political Economy of Agreement in Contemporary Art - Cem A. (Revista do Colóquio, 2026)
Cem A. diagnoses the current institutional climate of soft moral alignment, where art gestures toward politics without the difficulty of being political, and proposes strategic empathy as a potential path out.